2019
DOI: 10.3390/buildings9030071
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Acoustical Improvement and Surface Morphology of Seashell Composite Panel for Interior Applications in Buildings

Abstract: This manuscript focuses on the acoustical behaviors and surface morphology of seashell waste filler reinforced polyester (SFRP) coverings Anadara granosa Linn, Perna viridis Linn, and Placuna placenta Linn and applications in buildings. Their acoustical performances were observed using an impedance tube using a technique with two and four microphones based on ASTM E1050-98 and ASTM E2611-09. The improvements of acoustical performance were conducted by a coupled resonator inclusion with addition of a fibrous da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
3
2
0
Order By: Relevance
“…Although the sound absorption peaks of kenaf fiber are not as high as those of hemp fiber, kenaf can nonetheless be considered an acoustic material, especially for interior purposes. The findings are in agreement with other studies by Wang et al, Echeveria et al, and Setyowati et al [32] which concluded that the tailed cavity has function as a Helmholtz resonator and is very effective at absorbing sound energy in wide broadband frequencies [32,44,45].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Although the sound absorption peaks of kenaf fiber are not as high as those of hemp fiber, kenaf can nonetheless be considered an acoustic material, especially for interior purposes. The findings are in agreement with other studies by Wang et al, Echeveria et al, and Setyowati et al [32] which concluded that the tailed cavity has function as a Helmholtz resonator and is very effective at absorbing sound energy in wide broadband frequencies [32,44,45].…”
Section: Resultssupporting
confidence: 93%
“…Like the 30 mm thick samples, the 15 mm coco-husk with a single tailed cavity had absorption performance with a peak in 0.85 at 2.0 kHz, lower than the previous method of quarter wavelength resonators. Due to the cavity functioning like a Helmholtz resonator, such a finding is in agreement with previous studies by Setyowati et al, Echeverria et al and Wang et al [32,44,45]. Second, as Figure 8 indicates, we compared specimens treated with the present methods to the previous study observing coco-husks treated with quarter wavelength resonators and 10 mm air gaps.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This research not only focuses on porous hexagonal ceramic innovation by using water hyacinth powder in clay mixtures, in that it has the ability of absorption and material insulation but also compares the acoustic performance of porous ceramic with water hyacinth-based composites obtained in previous studies [1]. Meanwhile, several studies on acoustic materials from natural materials have also been carried out [2], [3].…”
Section: Introductionmentioning
confidence: 99%